The New Normal or More of the Same? Everyday Sexism and the Response of Traditional Media to an Internet Sensation during Lockdown - Susan Ball (Revue Française de Civilisation Britannique, 2023)
This article examines the responses of traditional media to an incident of everyday sexism that occurred in a town council meeting held online during the first lockdown of the Covid-19 pandemic. The incident received a brief period of notoriety consequent on the uploading on to Twitter of a 30-second video of the complete video of the meeting, which went viral during the third lockdown. The context for the incident and the media response is provided by the post-#MeToo era, during which feminist campaigns have persisted in drawing attention to the consequences of normalising everyday acts of sexism, and highlighted the need to tackle the cultural sexism of Western media. The normalisation of male abuse of women by traditional media is illustrated in the article by an examination of the tabloid press during the period of the first lockdown. In terms of practices of governance at the lowest level of representative democracy in England, the incident at the meeting occurred at a time when bullying, intimidation and harassment were a concern of the town council sector. The examination of a sample of traditional media reporting on the short video finds attention having been drawn to the video’s online success, which is mainly attributed to its amusement value. The female victim of abuse is portrayed as an unlikely celebrity, who then uses her media platform to deflect attention away from the realities of sexist bullying in local government. The case study illustrates attention having mainly been drawn to the workings of celebrity culture in the new normal of home working and video meetings, and a continuation of the longer standing normalisation of male abuse of women in some of the coverage by traditional media.